TINJAUAN IMPLEMENTASI MODEL TERINTEGRASI FOGARTY DALAM PEMBELAJARAN DI SEKOLAH DASAR - Putri, Arizkylia Yoka; Nani Mariana; Suryanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Learning in elementary schools is a crucial initial stage in the formation of the academic and social foundations of students, who are the main focus of applying Fogarty integrated models. This study aims to explore the implementation of Fogarty integrated learning models in the context of learning in elementary schools, with a focus on the theme "Water Resources in Daily Life." Descriptive qualitative research methods are used in this study by analyzing the design of integrated learning models from Fogarty in science, mathematics, social, and Indonesian subjects in elementary schools and their implementation. Data is collected through class observation, interviews with the teacher, and document analysis. The main findings show that the integrated learning model of Fogarty can stimulate students' enthusiasm for cross-subject learning but also reveal challenges in overcoming student confusion related to the complexity of the material. Further evaluation of the teaching methods used is needed to identify areas that need improvement, while additional support for students who experience difficulties also becomes crucial. In conclusion, the implementation of the integrated model of Fogarty has great potential for increasing the effectiveness of learning in elementary schools, but it requires sustainable efforts in the evaluation and adjustment of teaching methods to achieve optimal results